2006
DOI: 10.1007/s00705-006-0850-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational regulation of rotavirus protein NSP1 expression in mammalian cells

Abstract: The nonstructural rotavirus protein NSP1 binds specifically to viral mRNAs and to interferon regulatory factor 3 (IRF3), inducing IRF3 degradation through a proteasome-dependent pathway. By using a vaccinia virus expression system in mammalian cells, we found that the yield of NSP1 was 8- and 13-fold lower than the viral proteins VP2 or NSP3, respectively; while in the presence of proteasome inhibitors such difference could be reduced to 2- to 2.5-fold, respectively. The susceptibility of NSP1 to proteasome de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…In order to examine a possible role for NSP1 in STAT1 inhibition, we expressed the NSP1 proteins from three rotavirus strains (simian RRV, bovine UK, and murine EW) that share the common property of IRF3 degradation in HT29 cells (22) as GFP-tagged fusion proteins (23). Previous studies reported that NSP1 is a poorly expressed protein due to inefficient recruitment of ribosomes on NSP1 transcripts (42) and due to posttranslational NSP1 proteasomal degradation (23,37,43). Therefore, we chose a single-cell analytical approach to directly compare the pY701-STAT1 status within NSP1-expressing cells in the presence or absence of exogenous stimulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In order to examine a possible role for NSP1 in STAT1 inhibition, we expressed the NSP1 proteins from three rotavirus strains (simian RRV, bovine UK, and murine EW) that share the common property of IRF3 degradation in HT29 cells (22) as GFP-tagged fusion proteins (23). Previous studies reported that NSP1 is a poorly expressed protein due to inefficient recruitment of ribosomes on NSP1 transcripts (42) and due to posttranslational NSP1 proteasomal degradation (23,37,43). Therefore, we chose a single-cell analytical approach to directly compare the pY701-STAT1 status within NSP1-expressing cells in the presence or absence of exogenous stimulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NSP1 has several characteristics that suggest it functions as a viral E3 ubiquitin ligase. Primarily, NSP1 contains a RING domain similar to that of some E3 ligases (41,53,54), and the protein induces the proteasomal degradation of target proteins, such as IRF3 and IRF7 (37,53). Although the features of NSP1 indicate it functions as an E3 ubiquitin ligase, direct evidence in support of this has not yet been obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The antigen was rhesus rotavirus (strain RRV obtained from H. Greenberg, Stanford University, Palo Alto, California). Virus was cultivated in MA104 African green monkey (Cercopithecus aethiops) kidney cells as described previously (Pina-Vazquez et al, 2007). Virions from cell lysates were semipurified by ultracentrifugation and were then treated with EDTA to remove their outer layer, thereby exposing the group antigen, as described (Pina-Vazquez et al, 2007).…”
Section: Antirotavirus Enzyme Immunoassaymentioning
confidence: 99%
“…Virus was cultivated in MA104 African green monkey (Cercopithecus aethiops) kidney cells as described previously (Pina-Vazquez et al, 2007). Virions from cell lysates were semipurified by ultracentrifugation and were then treated with EDTA to remove their outer layer, thereby exposing the group antigen, as described (Pina-Vazquez et al, 2007). Double-shelled viral particles were concentrated by ultracentrifugation at 150,000 3 G in a SW50 rotor (Beckman, Palo Alto, California) and resuspended in 1/600th volume of Tris 50 mM, pH 8.0.…”
Section: Antirotavirus Enzyme Immunoassaymentioning
confidence: 99%
See 1 more Smart Citation